2005
DOI: 10.1016/j.ejvs.2004.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Aminoterminal Propeptide of Type III Procollagen and Matrix Metalloproteinases-2 and -9 Failed to Serve as Serum Markers for Abdominal Aortic Aneurysm

Abstract: Both MMP-2 and -9 and NIIINP failed to show relevance as serum markers for aortic dilatation. Our results are, therefore, in contradiction to previous published results. AAAs cannot be diagnosed with a simple blood test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 33 publications
2
35
1
1
Order By: Relevance
“…Sangiorgi et al reported higher serum levels of matrix metalloproteinase (MMP)-9 in patients with aortic aneurysm; however, a much larger study by Eugster and colleagues did not confirm these findings. 43,44 Although these aortic biopsy and blood assessments give clues as to the mechanisms taking place in end-stage AAA they cannot clarify the initiating pathways since many of the abnormalities demonstrated will be a consequence of the underlying pathological processes.…”
Section: Studies On Human Tissue and Serummentioning
confidence: 99%
“…Sangiorgi et al reported higher serum levels of matrix metalloproteinase (MMP)-9 in patients with aortic aneurysm; however, a much larger study by Eugster and colleagues did not confirm these findings. 43,44 Although these aortic biopsy and blood assessments give clues as to the mechanisms taking place in end-stage AAA they cannot clarify the initiating pathways since many of the abnormalities demonstrated will be a consequence of the underlying pathological processes.…”
Section: Studies On Human Tissue and Serummentioning
confidence: 99%
“…These include degradation products of elastin (18,19) and collagen (28), proteases (20,21), and inflammation markers such as cytokines (15,31) and c-reactive protein (27). However, a clear biomarker has yet to emerge, as these markers are not AAA specific, and many of the studies have conflicting results (8,23). Hence, there is urgent, unmet need for a sensitive and specific biomarker for AAA.…”
mentioning
confidence: 99%
“…23,24 However, these studies revealed contradictory conclusions. The present study showed that aging increases plasma active-MMP-9 level, but decreases the plasma pro-MMP-2 and NGAL-MMP-9 levels (Fig 8B).…”
Section: Discussionmentioning
confidence: 84%